دور السلطة الوطنية المستقلة في ضمان نزاهة العمليةالانتخابية في الجزائر - العياضي, عبد الجليل; حرابي, نصر الدين; الساكر, عمار (جامعة الوادي university el-oued, 2022)
إن نزاهة وشفافية العملية الانتخابية هي هدف تسعى إلى تحقيقه المجتمعات الديمقراطية، وذلك من خلال وجود آليات وضمانات لتحقيق تلك النزاهة، وغالبا ما يتم النص على تلك الضمانات في الدستور وتحكمها وتضبطها القوانين الانتخابية، التي تكفل الوسائل الملائمة والنظم المناسبة للوصول إلى عملية انتخابية تعبر بصورة صادق وحقيقية عن إرادة الناخبين وتحترم آراءهم وتحمي أصواتهم من كل ما قد يشوبها من تحريف أو تزوير أو تغيير. ولعل أهم تلك الضمانات هو ما تضمنه التعديل الدستوري لعام 2020 الذي نص على وجود إدارة مستقلة ممثلة في السلطة الوطنية المستقلة للانتخابات تشرف على جميع العمليات الانتخابية من بدايتها إلى غاية إعلان نتائجها، ويحكم عملها مبادئ مثل الحياد والاستقلالية لتصل إلى تحقيق عملية انتخابية نزيهة وشفافة، كما أن النظام الانتخابي الذي ينتهج أنماط وأساليب انتخابية سليمة ومدروسة هدفها الوحيد هو الحفاظ على صوت الناخب من كل تحريف أو تزوير هو النظام الانتخابي السليم، وهو الذي يضمن بجانب حق الانتخاب حقا آخر وهو الحق في الترشح، ويحدد شروطه وكيفياته بالطرق السليمة دون تعسف أو إقصاء، وهو ما حاول الأمر 21-01 النص عليه والأخذ به بغية الوصول إلى عملية انتخابية نزيهة وشفافة The integrity and transparency of the electoral process is a goal that democratic societies seek to achieve, through the existence of mechanisms and guarantees to achieve that integrity. It is true about the will of the voters, respects their opinions, and protects their votes from all that may be tainted by distortion, fraud or change. Perhaps the most important of these guarantees is what was included in the Constitutional Amendment of 2020, which stipulated the existence of an independent administration represented by the Independent National Elections Authority that supervises all electoral processes from its inception to the point of announcing its results, and its work is governed by principles such as neutrality and independence in order to achieve a fair and transparent electoral process, as well as The electoral system that adopts sound and studied electoral patterns and methods whose sole goal is to preserve the voter's vote from any distortion or fraud is a sound electoral system, which guarantees, in addition to the right to vote, another right, which is the right to run, and defines its conditions and modalities in the right ways without arbitrariness or exclusion. This is what Ordinance 21-01 tried to stipulate and adopt in order to reach a fair and transparent electoral process
مذكرة ماستر
Keywords: : الضمانات القانونية – العملية الانتخابية – أمر 21-01.; Legal guarantees - The electoral process - Order 21-01.